Determinants of primary market spread in developing securitization in Malaysia: a panel study / Mohammed Hariri Bakri - Bakri, Mohammed Hariri (2015)
Securitization is the process of transforming illiquid assets into rated long-term marketable securities that measures the relationship between securitized assets and market spread. The previous researches provided some evidences on the relationship between the nature of the assets and the primary market spread. Their models provide predictions on how other pricing characteristics affect US and Euro markets. However, emerging markets, notably Malaysia, remain to be testified, and hence these pending results have motivated this study to testify other tests with reference to the Vink Model to fill the literature gap. Further research found that although credit ratings are the most important variables to determine loan spread at issue date, investors appear not to rely exclusively on these ratings, as well as liquidity and leverage beyond the assigned credit rating. The first objective statement to provide empirical contribution variable such as Liquidity and Leverage as determinant of the primary market spread based on Vink regression model of2008 and 2012. The result shows that liquidity and leverage are significant determinant in the regression model. The next objective is to test the model of determinant of the primary market spread, the goodness fit model shows that all F-statistics are significant from models 1 to 6. Finally, the objective is to examine both internal (finn specific) and external (macroeconomic market condition) determinants of the primary market spread. It is interesting to note that the coefficients of the variable lose its explanatory power when other macroeconomic and financial indicators are controlled for. These results are testified as the study employs recently developed Panel Data approach and Least Method Regression analysis for the study periods of 2004-2012, eleven hypotheses support that their determinants have relationship with primary market spread. The results also verify that marketability characteristics represent the most important group in explaining loan spread variability in internal determinant. Likewise, the transaction size is the most important variables to determine loan spread at issue date. However, for macroeconomic market condition factor of determinants, capital structure characteristic plays main roles where interest and inflation are the main determinants for the primary market spread. As such, the study concludes that the selected determinants are helpful to issuers of bonds to offer alternative cheaper financing cost to their respective originators and better investment return to portfolio managers, and hence could stimulate the strong growth of the Malaysian securitization market in particular and capital market in general.